The Effectiveness of the Combination of Play Therapy and Speech Therapy on the Behavioral Development of Children With Autism Spectrum Disorder (ASD) - Heni Sumastri; Marta Pastari (Green Publisher Indonesia, 2022)
This study aims to analyze whether the combination of play therapy and speech therapy effectively affects the behavioral development of children with Autism Spectrum Disorder (ASD). This study uses a quantitative method with the population in this study are all children with autism who are regular visitors of speech therapy at NU_Kids Integrated Therapy 1 and 2. The collection of samples in this study used purposive sampling method. The results showed that most of the children who were given treatment only with speech therapy (Group I) had severe autism, namely 11 people (68.8%) then most of the children who were given combination treatment, namely combined speech therapy with play therapy (flash cards and puzzles). ) (Group II) also experienced severe autism, namely 9 people (56.3%). This shows that children with severe autism really need speech therapy to deal with the behavior disorders they experience.